2021
DOI: 10.1016/j.ipej.2021.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Premature ventricular contractions of the right ventricular outflow tract: is there an incipient underlying disease? New insights from a speckle tracking echocardiography study

Abstract: Context Premature ventricular contractions (PVCs) originating in the right ventricular outflow tract (RVOT) are traditionally considered idiopathic and benign. Echocardiographic conventional measurements are typically normal. Aims To assess whether right ventricle longitudinal strain, determined by two-dimensional speckle tracking echocardiography, differ between RVOT PVCs patients (treated with catheter ablation) and healthy controls. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…In fact, in a previous study we demonstrated that the use of three‐dimensional LGE increased the diagnostic yield of CMR to detect LVAs when compared to conventional two‐dimensional analysis, detecting fibrosis in three out of nine patients with LVAs (33%) of cases while two‐dimensional analysis failed to demonstrate fibrosis in all 19 . Also, using speckle tracking echocardiography in 21 patients with PVCs from the RVOT and in 13 control patients we were able to demonstrate the presence of worse RV longitudinal strain values (and therefore subclinical myocardial dysfunction) in the PVC group when compared to healthy controls 20 . But on the other hand, the presence of LVAs does not necessarily mean presence of fibrosis.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…In fact, in a previous study we demonstrated that the use of three‐dimensional LGE increased the diagnostic yield of CMR to detect LVAs when compared to conventional two‐dimensional analysis, detecting fibrosis in three out of nine patients with LVAs (33%) of cases while two‐dimensional analysis failed to demonstrate fibrosis in all 19 . Also, using speckle tracking echocardiography in 21 patients with PVCs from the RVOT and in 13 control patients we were able to demonstrate the presence of worse RV longitudinal strain values (and therefore subclinical myocardial dysfunction) in the PVC group when compared to healthy controls 20 . But on the other hand, the presence of LVAs does not necessarily mean presence of fibrosis.…”
Section: Discussionmentioning
confidence: 78%
“…19 Also, using speckle tracking echocardiography in 21 patients with PVCs from the RVOT and in 13 control patients we were able to demonstrate the presence of worse RV longitudinal strain values (and therefore subclinical myocardial dysfunction) in the PVC group when compared to healthy controls. 20 But on the other hand, the presence of LVAs does not And yet currently, there is no reliable method for the diagnosis of these minimal abnormalities identified as LVAs so far. So, the identification of a noninvasive marker of LVAs is important.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the type of interstitial fibrosis that occurs in the initial phases of ARVC is not reliably detected with CMR with LGE (Puntmann et al, 2016). Using two-dimensional speckle tracking echocardiography (2D-STE) Fonseca et al (2021) in a previous study have demonstrated that the right ventricle global longitudinal strain was significantly lower in patients with RVOT PVCs when compared with a control group, irrespective of the previous PVCs burden and success of the catheter ablation procedure. Concerning strain values determined by CMR, Zghaib et al (2018) have previously demonstrated, in ARVC patients, that lower regional strain could identify low voltage areas on endocardial and epicardial electroanatomical mapping and had a better correlation with VT substrate than late gadolinium enhancement sites.…”
Section: Discussionmentioning
confidence: 99%
“…Whether these LVAs correspond to a form of incipient manifestation of a disease of the RVOT remains unproved. Also, it was previously pointed out that patients with frequent PVCs had worse RV global longitudinal strain values (and therefore sub-clinical myocardial dysfunction) than healthy controls patients with structurally apparent normal hearts, irrespective of the absence of abnormalities on the CMR (Fonseca et al, 2021). Fibrosis is associated with late local activation and areas of slow conduction and slower wavefront propagation speed, known as deceleration zones (DZ) (Raiman and Tung, 2018;Aziz et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies reported that LV-GLS values were signi cantly decreased in patients with frequent PVCs and preserved LVEF [19][20][21]. Studies evaluating the effects of RF ablation on LV-GLS in patients with preserved LVEF are limited.…”
Section: Pvc-cm Was Rst Classi Ed As An Indication Of Catheter Ablati...mentioning
confidence: 99%